Applied investigation of methyl, ethyl, propyl, and butyl mercaptan as potential poisons in the gas phase polymerization reaction of propylene (2024)
The polypropylene (PP) synthesis process is crucial in the plastics industry, requiring precise control as it directly impacts the catalytic activity and the final product’s performance. This study investigates the effects of trace amounts of four different mercaptans on the polymerization of propylene using a fourth-generation Ziegler–Natta (ZN) catalyst. Various concentrations of these mercaptans were tested, and results showed that their presence significantly reduced the melt flow index (MFI) of the final PP. The most notable MFI decrease occurred at 37.17 ppm of propyl mercaptan and 52.60 ppm of butyl mercaptan. Methyl and ethyl mercaptan also reduced the MFI at lower concentrations, indicating that mercaptans act as inhibitors by slowing down the polymerization process and reducing the fluidity of molten PP. The highest MFI increase was observed at lower concentrations of each mercaptan, suggesting that smaller molecular inhibitors require less concentration. This trend was also seen in the catalyst’s productivity, where lower concentrations of methyl mercaptan reduced PP production more effectively than higher concentrations of butyl mercaptan. Fourier transform infrared spectroscopy (FTIR) identified interactions between the mercaptans and the ZN catalyst. Computational analysis further supported these findings, providing insights into the molecular interactions and suggesting possible inhibition mechanisms that could impact the final properties of polypropylene.